PENGARUH PENYALURAN KREDIT, DANA LAINNYA DAN PENDAPATAN PERBANKAN TERHADAP PERUBAHAN MODAL PADA PT. BANK TABUNGAN NEGARA(PERSERO) TBK. - Aang Syahdina (Jurnal Akuntansi Bisnis, 2017)
In this study, the authors examined the influence of Distribution of credit, other Funds and bank profits to changes in capital in PT. Bank Tabungan Negara (Persero) Tbk.  And to analyze data Distribution of  credit, other funds, Bank  profits and Changes in Capital authors take data on the Financial Statements PT. Bank Tabungan Negara (Persero) Tbk period 2002-2010 per quarter. In this study, there are three variables, namely the distribution of credit, other funds (X1), bank profits (X2) as independent variables and Changes in Capital (Y) as the dependent variable. The research method used by the authors is associative method which aims to determine the causal relationship between two or more variables.Literature used in this study, among others through the study of libraries,data obtained from the central office at PT.Bank Tabungan Negara (Persero) Tbk, and onother-another.The purpose of this study was to determine influence the distribution of credit, other funds, bank profit to the changes in capital.Keywords: Distribution of credit, other Funds, Bank Profits, and Changes in Capital.